Carpenters and Joiners entrance card, 1897 (1897)
1897 1880-1914 "Carpenters and Joiners entrance card, 1897" [T0270.jpg], 1897 Amalgamated Society of Carpenters and Joiners entrance card belonging to William Smith, who joined the Atherton and Tyldesley Branch near Bolton on 30 July 1897.